Causes, Origins and Possible Effects of the ASEAN Economic Community (AEC) - Pasierbiak, Pawel Mariusz (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2018)
In 2007, the Association of Southeast Asian Nations (ASEAN) at its 13th summit decided to create the ASEAN Economic Community (AEC). In assumptions, the common market was to be established by the end of 2015, and the introduction of free movement of goods, services, capital and skilled labor was to lead to an increase in the degree of market integration among member states. But the creation of a single market is not an easy process, as illustrated by the case of the European Community/European Union, where a process of single market creation has been implemented slowly and with numerous difficulties. On the other hand, if the process of a common market creation is successful, the integration brings benefits to the participating countries. The primary goal of this article is to indicate potential effects as well as to show the progress of the implementation and functioning of the common market in the ASEAN Economic Community. To achieve the objective, the author will analyze the theoretical implications of a common market and the real implications, taking the European Union as an example. Having done this part of the analysis, the author will try to indicate and evaluate the possible effects of the process of the common market creation in the Association of Southeast Asian Nations.